Game changer or accounting practice? Gender responsive budgeting in India. Issue 7 (3rd October 2021) - Sushant,; Laha, Moumita
IMPACT: Gender responsive budgeting is a process to achieve gender mainstreaming. Since India's first gender budget statement was published in 2005/06, the country's gender budget increased more than eight-fold in 2018/19. Using quantitative and qualitative data, this article highlights several procedural issues and 'grey' areas that require the attention of policy-makers. The over-arching message of the study is that GRB in India is an elementary exercise with limited strategic direction. The capacity of officials responsible for producing GBs is questionable and further training is needed. Sensitization to the needs and priorities of women would significantly contribute to gender mainstreaming and policy refinements. ABSTRACT: Gender responsive budgeting (GRB) is a process to enhance gender equality through financial allocations in government budgets. The objective of the study was to understand trends in India's government's ministries and departments. The total gender budget (GB) exhibited strong growth between 2007/08 and 2018/19. However, the GB for 'women-specific programmes' had moderate growth. This article highlights a policy–practice gap and contributes to the scarce literature on GRB in India. The authors advocate the use of GBs for strategic outcomes that promote gender mainstreaming.